2015
DOI: 10.1021/acsami.5b03310
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Anisotropic Assembly of Conjugated Polymers in Insulating Polymer Blends

Abstract: Low-dose UV irradiation of poly(3-hexylthiophene) (P3HT)-insulating polymer (polystyrene (PS) or polyisobutylene (PIB)) blend solutions led to the formation of highly ordered P3HT nanofibrillar structures in solidified thin films. The P3HT nanofibers were effectively interconnected through P3HT islands phase-separated from insulating polymer regions in blend films comprising a relatively low fraction of P3HT. Films prepared with a P3HT content as low as 5 wt % exhibited excellent macroscopic charge transport c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 45 publications
3
80
0
Order By: Relevance
“…24,32 This isotropic morphology or lack of anisotropy is consistent with the AFM images (Figure 2A,B). In contrast, both randomly oriented and shear-aligned P3HT 24,32 However, the birefringent textures of shearaligned P3HT NWs display higher brightness compared to the randomly oriented P3HT NWs, which is primarily due to enhancement in the anisotropy. The birefringent brightness of shear-aligned P3HT NWs increases as a function of the shearing speed in the following order: 4.0 mm/s < 0.5 mm/s < 2.0 mm/s < 1.0 mm/s.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…24,32 This isotropic morphology or lack of anisotropy is consistent with the AFM images (Figure 2A,B). In contrast, both randomly oriented and shear-aligned P3HT 24,32 However, the birefringent textures of shearaligned P3HT NWs display higher brightness compared to the randomly oriented P3HT NWs, which is primarily due to enhancement in the anisotropy. The birefringent brightness of shear-aligned P3HT NWs increases as a function of the shearing speed in the following order: 4.0 mm/s < 0.5 mm/s < 2.0 mm/s < 1.0 mm/s.…”
Section: Resultssupporting
confidence: 87%
“…The slow shearing speed presumably allows for the slow evaporation rate of the solvent and provides polymer chains and NWs to reach an equilibrium rate. 7,21,32,35 Quantitative modeling of the absorption spectra was employed to probe the intramolecular ordering and effective conjugation length of the polymer chains. [22][23][24]36 Two phases are observed in the P3HT absorption spectrum that correlate with a crystalline phase and an amorphous phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[246] The chain-like nanowires were observed to be distributed homogenously in the PS/CH 2 Cl 2 solution and did not further aggregate during solvent evaporation and subsequent vitrification of PS. [275] The authors suggested that the presence of PS chains facilitated the formation of molecular interactions between P3HTs in the UV irradiation process, and enhanced interactions between P3HT chains during spin coating, because of the relatively unfavorable P3HT−PS chain interactions. The P3HT nanofibrilar network kept the connection of charge pathways at the channel so effectively that the percolation threshold of the blend was below 1 wt% P3HT.…”
Section: Blend Films With Embedded Semiconductor Nanowiresmentioning
confidence: 99%
“…With such an approach, the nozzle clog problem, which frequently occurs during inkjet printing of long-chain polymers with high viscoelasticity, can be avoided. [275] Copyright 2015, American Chemical Society. Wang and coworkers showed the ability to control the crosslinking density and thus solubility of the pre-deposited PS layer by adjusting the UV irradiation time.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%